Impact of the COVID-19 pandemic on access to and delivery of maternal and child healthcare services in low-and middle-income countries: a systematic review of the literature - Kuandyk (Sabitova), Alina; Ortega, Miguel-Angel; Ntegwa, Magashi Joseph; Sarria-Santamera, Antonio (Frontiers in Public Health, 2024)
Background The COVID-19 pandemic has had a multifaceted impact on maternal and child services and adversely influenced pregnancy outcomes. This systematic review aims to determine the impact of the COVID-19 pandemic on access to and delivery of maternal and child healthcare services in low- and middle-income countries. Methods The review was reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A primary search of electronic databases was performed using a combination of search terms related to the following areas of interest: “impact’ AND ‘COVID-19’ AND ‘maternal and child health services’ AND ‘low- and middle-income countries. A narrative synthesis approach was used to analyse and integrate the results. Results Overall, 45 unique studies conducted across 28 low- and middle-income countries met the inclusion criteria for the review. The findings suggest the number of family planning visits, antenatal and postnatal care visits, consultations for sick children, paediatric emergency visits and child immunisation levels decreased compared to the pre-pandemic levels in the majority of included studies. An analytical framework including four main categories was developed based on the concepts that emerged from included studies: the anxiety of not knowing (1), overwhelmed healthcare systems (2), challenges perceived by healthcare professionals (3) and difficulties perceived by service users (4). Conclusion The COVID-19 pandemic disrupted family planning services, antenatal and postnatal care coverage, and emergency and routine child services. Generalised conclusions are tentative due to the heterogeneity and inconsistent quality of the included studies. Future research is recommended to define the pandemic’s impact on women and children worldwide and prepare healthcare systems for future resurgences of COVID-19 and potential challenges beyond. Systematic review registration PROSPERO (CRD42021285178).